Effects of different fat sources on growth performance of early-weaned pigs - De La Llata, M.; Grinstead, G.S.; Woodworth, J.C.; Herbert, J.S.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and eighty weanling pigs (initially 14.6 lb and 21 ± 2 d of age) were used in a 35 d growth trial to evaluate different dietary fat sources. Treatments consisted of a control diet (no added fat) or diets with 5% added fish oil, soybean oil, choice white grease, or a combination of 2.5% fish oil and 2.5% choice white grease. The diets were fed in two phases (d 0 to 14 and d 14 to 35 after weaning). Diets were fed in a meal form and formulated to a similar lysine:calorie ratio. From d 0 to 14 after weaning, pigs fed either soybean oil or fish oil had improved ADG and F/G compared to pigs fed the control diet, with those fed choice white grease or the blend of choice white grease and fish oil having intermediate performance. From d 14 to 35 and for the cumulative period (d 0 to 35) after weaning, neither added fat nor source affected ADG; however, F/G was improved for pigs fed any of the fat sources compared with those fed the control diet. These results suggest that adding 5% fat to the diet from d 0 to 35 .after weaning improved F/G approximately 8%. Fish oil, soybean oil, and choice white grease appear to be similar in their value as fat sources for weanling pigs.
Keywords: Swine; Fat source; Early-weaned pigs; Performance